Technology enhanced problem based learning - Zaphiris, Panayiotis; Arh, Tanja; Klobučar, Tomaž; Ioannou, Andri; Vasiliou, Christina (My University, 2013)
Problem based learning (PBL) pedagogy aims to provide context-rich academic situations where students can work together and demonstrate authentic application of knowledge. This paper seeks to address a recurrent problem in education related to the implementation of PBL pedagogy that students are often disengaged from active collaboration, fertile discussion, physical interaction around emerging group artefacts, and reflection. The success of PBL implementation depends on both the selection of learning activities and development of appropriate infrastructure - learning spaces in which the activities can take place. Yet, the technologies often comprising the PBL learning space in the university classroom (e.g., projector, laptops, vertical smart board) and the way they are being used by instructors and learners seem to hinder the successful implementation of PBL.
Keywords: Pedagogy; Technologies; Problem based learning (PBL)